SINERGI ANTARA MANAJEMEN PENDIDIKAN DAN PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KOMPETENSI SPIRITUAL SISWA DI SMP MA’ARIF 01 KOTA PASURUAN - Akhmad Zubaidillah; M. Fahmi Adam; Robbiatul Amalia; Tarisya Chairana Mahiira (LP2M IAIN Sultan Amai Gorontalo, 2024)
Education not only plays a role in building academic intelligence, but also in shaping students' morality and spirituality. This research explores the synergy between school management and Islamic Religious Education (PAI) in improving students' spiritual competence. Using a qualitative case study approach, this research asks the question: how does collaboration between school management and PAI teachers contribute to the formation of students' spirituality? Data was obtained through in-depth interviews, observation and documentation at a school that implemented an integrated religious program. The research results show that school management support that is in line with the example of PAI teachers creates an environment that supports students' spiritual development. This synergy not only enriches students' understanding of religion, but also builds moral values ​​in their daily lives. This research has a significant impact in developing an educational model that prioritizes spirituality, relevant for schools that want to strengthen students' spiritual competence through a collaborative and sustainable approach.